2020
DOI: 10.37705/techtrans/e2020025
|View full text |Cite
|
Sign up to set email alerts
|

Risk management analysis in construction enterprises in selected regions in Poland

Abstract: This paper aims to outline the selected issues of risk management in construction enterprises operating in the Silesian and Małopolskie voivodships (Poland). In this context, it seems vitally important to have risk accurately identified, quantified and, consequently, responded to in the right way. Although the paper is mainly empirical in its character, it is based on a theoretical background, particularly when it comes to risk management in the construction industry, which is referred to in the literature on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
0
12
0
2
Order By: Relevance
“…An extreme way of handling risk in the construction industry is making a decision not to perform high-risk works. The results of the empirical studies from 2016, however, show that 47% of contractors agree to perform even high risk construction projects (Myrczek, and Tworek, 2019;Myrczek et al, 2020). In the research the respondents indicated some reasons for taking up risky construction projects.…”
Section: Responses To Risk As An Element Of Risk Management Process Imentioning
confidence: 84%
See 4 more Smart Citations
“…An extreme way of handling risk in the construction industry is making a decision not to perform high-risk works. The results of the empirical studies from 2016, however, show that 47% of contractors agree to perform even high risk construction projects (Myrczek, and Tworek, 2019;Myrczek et al, 2020). In the research the respondents indicated some reasons for taking up risky construction projects.…”
Section: Responses To Risk As An Element Of Risk Management Process Imentioning
confidence: 84%
“…These included: ensuring healthy cashflow (4 contractors), maintenance of high turnover figures (2 contractors), financial reasons (2 contractors), the belief that risk can be eliminated (2 contractors), an investment project with a relatively late delivery date (1 contractor), a high value investment project (1 contractor), the prestige given by the project -the renovation of Auschwitz (1 contractor), the need to perform a given task (1 contractor), an investment project with highly filled order portfolio (1 contractor), poor market conditions -a small number of tenders (1 contractor), good construction practice (1 contractor), a big number of employees (1 contractor), more lucrative works (1 contractor), the company's position on the market (1 contractor), the investor's insolvency (1 contractor), technical documentation (1 contractor). Such arguments allow us to get a better understanding of the motives behind construction contractors' practical decisions, although only 9% of them agreed to absorb all the risk (Myrczek, and Tworek, 2019;Myrczek et al, 2020). As many as 38% of the contractors eliminate risks, 34% of the respondents mitigate risks, while 13% of them transfer risk onto other participants of investment and construction processes (Myrczek, and Tworek, 2019;Myrczek et al, 2020).…”
Section: Responses To Risk As An Element Of Risk Management Process Imentioning
confidence: 99%
See 3 more Smart Citations